Analisis Kepuasan Pengguna Sistem Informasi Akademik dalam Perspektif Manajemen di Politeknik Negeri Sriwijaya - Putra, Erlangga Kesuma; Antoni, Darius; Akbar, Muhamad (FKOM UNIKU, 2020)
Userâ€™s Satisfaction is one of the keys to the success of an Information System. This study aims to analyze the satisfaction of Academic Information System Users in the State Polytechnic of Sriwijaya based on organizational culture variables and the quality of the information system to the satisfaction of information system users and their implications for employee performance. Data analysis involves 71 participants who come from education personnel with variations in Gender, Age, Latest Education and Years of Service. Data analysis uses CFA of Exogenous and Endogenous Constructions and SEM Partial Least Square (PLS). The final results obtaine conclusion that Organizational Culture Variables have a positive and it do not have significant effect on the satisfaction towards the use of Information Systems while the Quality of Information Systems variable has a positive and significant effect on the Satisfaction towards the Use of Information Systems of Â State Polytechnic of Sriwijaya Palembang.Keywords â€“ CIO, User Satisfaction, Information System Management